Broad-spectrum Investigational Agent GS-5734 for the Treatment of Ebola, MERS Coronavirus and Other Pathogenic Viral Infections with High Outbreak Potential. (4th October 2017) - Jordan, Robert; Hogg, Alison; Warren, Travis; De Wit, Emmie; Sheahan, Timothy; Lo, Michael; Soloveva, Veronica; Weidner, Jessica; Gomba, Laura; Feldmann, Friederike; Cronin, Jacqueline; Sims, Amy; et al.
Abstract: Background: Recent viral outbreaks with significant mortality such as Ebola virus (EBOV), SARS-coronavirus (CoV), and MERS-CoV reinforced the need for effective antiviral therapeutics to control future epidemics. GS-5734 is a novel nucleotide analog prodrug in the development for treatment of EBOV. Method: Antiviral activity of GS-5734 has been established in vitro against a wide range of pathogenic RNA virus families, including filoviruses, coronaviruses, and paramyxoviruses (EC50  = 37 to 200 nM) ( Warren et al., Nature 2016; Sheahan et al., Sci Transl Med 2017; Lo et al., Sci Rep 2017 ). Herein, we describe the in vivo translation of the broad-spectrum activity of GS-5734 in relevant animal disease models for Ebola, Marburg, MERS-CoV, and Nipah. Result: Therapeutic efficacy against multiple filoviruses with 80–100% survival was observed in rhesus monkeys infected with lethal doses of EBOV (Kikwit/1995 or Makona/2014) or Marburg virus and treated with once daily intravenous (IV) administration of 5 to 10 mg/kg GS-5734 beginning 3 to 5 days post-infection (p.i.). In all rhesus monkey filovirus infection models, GS-5734 significantly reduced systemic viremia and ameliorated severe clinical disease signs and anatomic pathology. In mice infected with MERS-CoV, twice daily subcutaneous administration of 25 mg/kg GS-5734 beginning 1 day p.i. significantly reduced lung viral load and improved respiratory function. In rhesus monkeys, once-daily IV administration of 5 mg/kg GS-5734 initiated 1 day prior to MERS-CoV infection reduced lung viral load, improved clinical disease signs, and ameliorated severe lung pathology. Finally, in African green monkeys infected with a lethal dose of Nipah virus therapeutic once-daily IV administration of 10 mg/kg GS-5734, starting 1 day p.i. resulted in 100% survival to at least day 35 without any major respiratory or CNS symptoms. Conclusion: GS-5734 is currently being tested in a phase 2 study in male Ebola survivors with persistent viral RNA in semen. Lyophilized drug formulation has been developed that can be administered to humans via a 30-minutes IV infusion and does not require cold chain storage. Together, these results support further development of GS-5734 as a broad-spectrum antiviral to treat viral infections with high mortality and significant outbreak potential. Disclosures: R. Jordan, Gilead: Employee, Salary. J. Feng, Gilead: Employee,  Salary I. Trantcheva, Gilead: Employee, Salary. D. Babusis, Gilead: Employee, Salary. D. Porter-Poulin, Gilead: Employee, Salary. R. Bannister, Gilead: Employee,  Salary R. Mackman, Gilead: Employee, Salary. D. Siegel, Gilead: Employee,  Salary A. Ray, Gilead: Employee, Salary, T. Cihlar, Gilead: Employee, Salary.